Reduction of Antibiotic Prescription in Complicated Appendicitis through Behavioral Change Measures - Artiles Garcia, Alberto A.; Guanche Garcell, Humberto; Pinto Echevarría, Miguel J.; Sanchez Portela, Carlos A.; Sanchez Rivas, Carlos M.; Arias Medina, Marlon; Seoane Perez, Niuvis; Escobar More, Osiris I.; Fernandez Hernandez, Tania M. (Avicenna Journal of Medicine, 2024)
Background Variability in the prescription of antibiotics constitutes an area for improvement related to patient safety issues, including the risk of infection and health care efficiency based on evidence.Objectives The study aims to evaluate the effect of an intervention to reduce the duration of antibiotic treatment in complicated appendicitis.Methods A quality improvement program was implemented in the surgical department of The Cuban Hospital (Doha, Qatar). During a 3-month baseline period, data about antibiotic duration, consumption (daily defined doses), and cost (in Qatary Riyals) were identified, as well as during two plan-do-study-act (PDSA) intervention periods. Interventions include action focused on staff education, monitoring antibiotic use, feedback, and reminders during discharge planning.Results At baseline, 13 patients with complicated appendicitis were documented, while there were 41 and 15 patients during PDSA cycles 1 and 2, respectively. A 29.5% reduction in days of antibiotic treatment was observed during the PDSA cycle 2 in comparison with the baseline. Accordingly, a reduction of 38.7% in the consumption of antibiotics and a reduction of 24.6% in cost were observed, with no adverse outcomes for patients during the 30-day follow-up period.Conclusion The intervention resulted in an improvement in antibiotic use with satisfactory patient outcomes and an additional effect on the efficiency of health care and the prevention of microbial resistance and other adverse effects.
Keywords: appendicitis; complicated; antibiotics; intervention; cost; behavioral change